Down-regulation of cell membrane localized NTCP expression in proliferating hepatocytes prevents hepatitis B virus infection - Ying Yan; Lena Allweiss; Danli Yang; Jingting Kang; Jianwen Wang; Xiangjun Qian; Ting Zhang; Hui Liu; Lu Wang; Shuhong Liu; Jianhua Sui; Xiangmei Chen; et al. (Emerging Microbes and Infections, 2019)
ABSTRACTHepatocyte proliferation could result in the loss of covalently closed circular DNA (cccDNA) and the emergence of cccDNA-cleared nascent hepatocytes, which appear refractory to hepatitis B virus (HBV) reinfection with unknown mechanism(s). Sodium taurocholate cotransporting polypeptide (NTCP) is the functional receptor for HBV entry. In this study, down-regulation of cell membrane localized NTCP expression in proliferating hepatocytes was found to prevent HBV infection in HepG2-NTCP-tet cells and in liver-humanized mice. In patients, lower NTCP protein expression was correlated well with higher levels of hepatocyte proliferation and less HBsAg expression in HBV-related focal nodular hyperplasia (FNH) tissues. Clinically, significantly lower NTCP protein expression was correlated with more active hepatocyte proliferation in CHB patients with severe active necroinflammation and better antiviral treatment outcome. Mechanistically, the activation of cell cycle regulatory genes p53, S-phase kinase-associated protein 2 (SKP2) and cyclin D1 during cell proliferation, as well as proliferative and inflammatory cytokine Interleukin-6 (IL-6) could transcriptionally down-regulate NTCP expression. From these aspects, we conclude that within the milieu of hepatocyte proliferation, down-regulation of cell membrane localized NTCP expression level renders nascent hepatocytes resistant to HBV reinfection. This may accelerate virus clearance during immune-mediated cell death and compensatory proliferation of survival hepatocytes.